2004
DOI: 10.1097/01.asn.0000146688.74084.a3
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Iothalamate-GFR and Serum Creatinine-Based Outcomes

Abstract: Abstract. In renal clinical trials, both slope-based and timeto-event renal outcomes have been used. These outcomes are typically based on estimates of GFR obtained using creatinine or iothalamate GFR (iGFR). The African American Study of Kidney Disease and Hypertension (AASK) was a trial in 1094 African Americans with hypertensive nephrosclerosis, which examined the effects of two levels of BP control and three antihypertensive regimens. This study compared the effects of the AASK interventions on outcomes ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
38
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 22 publications
5
38
1
Order By: Relevance
“…The rate of GFR loss varies from patient to patient, even among patients with the same renal disease, but for a given patient, the rate is generally believed to be constant (5). Recently, however, it was suggested that the decline slope may accelerate late in the course of chronic kidney disease (CKD) (6). Despite improved therapies in recent years with angiotensin antagonist therapy and aggressive BP control, many patients continue to lose renal function and ultimately reach ESRD.…”
mentioning
confidence: 99%
“…The rate of GFR loss varies from patient to patient, even among patients with the same renal disease, but for a given patient, the rate is generally believed to be constant (5). Recently, however, it was suggested that the decline slope may accelerate late in the course of chronic kidney disease (CKD) (6). Despite improved therapies in recent years with angiotensin antagonist therapy and aggressive BP control, many patients continue to lose renal function and ultimately reach ESRD.…”
mentioning
confidence: 99%
“…eGFR levels were derived from the re-expressed MDRD Study formula, namely, 175 ϫ (serum creatinine value) Ϫ1.154 ϫ age Ϫ0.203 ϫ 0.742 (if female) ϫ 1.21 (if black) (10). An additional equation was used for black participants, the specific equation developed at the baseline evaluation for AASK, relating clearance of I 125 -iothalamate to serum creatinine, gender, and age: eGFR ϭ 329 ϫ creatinine Ϫ 1.096 ϫ age Ϫ 0.294 ϫ 0.736 (if female) (11). Because body mass index was higher for black individuals, we also used eGFR estimates, unadjusted for body surface area (BSA), by multiplying each patient's eGFR by BSA and dividing by 1.73 m 2 .…”
mentioning
confidence: 99%
“…For example, patients with muscle mass that is higher than average for their age, sex, and race will have an average eGFR Cr that is lower than true GFR, and patients with muscle mass that is lower than average for their age, sex, and race will have an average eGFR Cr that is higher than true GFR. Error is best determined by the test-retest reliability, which does not appear to differ much between eGFR and mGFR (10,47). To the extent that eGFR error is similar in magnitude to mGFR error, differences in method precision do not explain stronger associations with eGFR compared with mGFR.…”
Section: Imprecision With Mgfr Is a Problem That Can Be Adequately Admentioning
confidence: 99%